Antropokozmički vidici slobode u filozofiji znanosti / Anthropocosmic Freedom Horizons in the Philosophy of Science - Mahmutćehajić, Rusmir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2025)
The text body of this essay corresponds to the paper the author presented in the International Academy of Sciences and Arts in Bosnia and Herzegovina on 25 May 2024, on the occasion of becoming a laureate as a recognition of author’s scientific opus and excellence.